KESETARAAN GENDER DITINJAU DARI PERKEMBANGAN HUKUM WARIS BAGI PEREMPUAN BALI - Ida Ayu Putu Sri Astiti Padmawati, SH.,MH.; Ida Bagus Sudarma Putra (VYAVAHARA DUTA, 2023)
Balinese society with a patrilineal kinship system (in Bali it is better known as purusa or kapurusa), is always interesting to provide material for discussion, especially when it is associated with the position of women in the family and society. The existence of Balinese women, in various aspects of life, is felt to be in a position that does not reflect gender equality and justice. The Kapusa system adopted is "cornered" as the main cause of creating an unfavorable atmosphere for Balinese women, especially in the distribution of inheritance. the research used is normative legal research methods, with a statutory approach (The statue approach) and the Conceptual Approach (The Conceptual Approach). Sources of legal materials that will be used to support the discussion of the above issues are primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study are the Decision of the Pesamuhan Agung MUDP (Majelis Utama Desa Pakraman) Bali Number 01/KEP/PSM-3/MDP Bali/X/2010 dated 15 October 2010 concerning the Results of the Grand Assembly III of the Main Council of Pakraman Village Bali can bring changes that are fundamental to the regulation of Balinese customary inheritance law. The decision of the Pesamuhan Agung gave Balinese women inheritance rights over the gunakaya inheritance left by the heir. Although the Decision of the Pesamuhan Agung does not stipulate the distribution of rights for women and men equally as the sense of justice itself, for the people of Bali this is an extraordinary change, and therefore it needs to be socialized more clearly so that it can be fully and comprehensively understood by all levels of society. Balinese customary law communities including local governments and law enforcers. Keywords: Gender Equality, Women, inheritance rights.